2022
DOI: 10.3390/ijms23147766
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into TRP Ion Channels in Stem Cells

Abstract: Transient receptor potential (TRP) ion channels are cationic permeable proteins located on the plasma membrane. TRPs are cellular sensors for perceiving diverse physical and/or chemical stimuli; thus, serving various critical physiological functions, including chemo-sensation, hearing, homeostasis, mechano-sensation, pain, taste, thermoregulation, vision, and even carcinogenesis. Dysregulated TRPs are found to be linked to many human hereditary diseases. Recent studies indicate that TRP ion channels are not on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…In order to provide significant and personalized therapeutic strategies for patients with high-grade gliomas, it is therefore necessary to accurately identify different GSC subtypes in high-grade gliomas. Increasing evidence has revealed that several ion channels belonging to the transient receptor potential (TRP) family are heterogeneously expressed in different types of cancer stem cells (CSCs); however, information on GSCs is limited [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to provide significant and personalized therapeutic strategies for patients with high-grade gliomas, it is therefore necessary to accurately identify different GSC subtypes in high-grade gliomas. Increasing evidence has revealed that several ion channels belonging to the transient receptor potential (TRP) family are heterogeneously expressed in different types of cancer stem cells (CSCs); however, information on GSCs is limited [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“… 150 Interestingly, studies have shown that miR-204 is substantially down-regulated due to hypermethylation of the TRPM3 promoter, which is related to enhanced cell stemness and migration. 137 In addition, in nude mouse brain transplant tumors, miR-204 restoration consistently inhibited tumor invasion and improved animal survival. 63 However, the role of TRPM3 and the regulatory function of miR-204 have been questioned.…”
Section: Signaling Pathways Of the Trpm Channels In Gliomamentioning
confidence: 98%
“… 63 Furthermore, DNA methylation of the TRPM3 promoter was positively correlated with glioma dryness and migration. 137 Moreover, TRPM3 has also been closely related to glioma growth and autophagy, 138 but its mechanism needs further research. In conclusion, methylation of the TRPM3 is involved in the malignant phenotype of glioma.…”
Section: Pathological Functions Of the Trpm Channels In Gliomamentioning
confidence: 99%
“…Some TRP affect skeletal calcium homeostasis interfering with intestinal calcium absorption (TRPV6), renal calcium reabsorption (TRPV5), OC differentiation (TRPV1,2,4,5) and chondrocytes (TRPV4) [ 29 ]. Furthermore, TRPV4, TRPA1 and TRPM7 are present in MSC together with the entire TRPC group and may regulate stem cells physiology and differentiation [ 129 ]. TRP are associated to bone resorption and osteoblast functions with a direct impact on osteoblastic and osteoclastic marker genes collagen 1 (COL1), ALP, osteocalcin (OCN), osteopontin (OPN), bone sialoprotein, Runx2, Cox2, c-Fos, tartrate-resistant acid phosphatase (TRAP), OPG/RANKL and NFATc1 [ 27 , 29 , 130 ].…”
Section: Ion Channels As Membrane Multi-sensors and Transducers In Bo...mentioning
confidence: 99%